Sunflower lines originated from varieties with high oil content in their seed - V. A. Gavrilova; I. N. Anisimova; T. G. Stupnikova (Труды по прикладной ботанике, генетике и селекции)
Background. Sunflower as an oilseed crop originated from Russia. It was in this country that single-headed highly productive forms were obtained, industrial oil production was invented, first local varieties were developed, accessions with increased oil content in seeds were identified by V. S. Pustovoit and his associates, and the first high-yielding cultivars ('Peredovik', 'VNIIMK 8883') with high oil content in seeds (50-60%) were produced. Mutants with modified fatty acid composition were obtained, and high oleic cultivar 'Pervenets' was created. Soviet varieties formed the basis for the world's sunflower breeding, and further for breeding commercial hybrids using the effect of heterosis. In the article, the genetic diversity of lines originated from domestic varieties is demonstrated. The genealogy of many domestic lines and also of the American line HA89 which served as the reference in breeding trials and genetic experiments is discussed. The information on the lines developed by the researchers of VIR at Kuban Experiment Station in the years 1970-2015 as well as the available data of foreign researchers on the lines obtained from domestic varieties are presented.Materials and methods. The lines were developed using repeated self pollination of the varieties and selection by morphological characters, CMS, pollen fertility restoration ability, duration of the growing season, and downy mildew resistance in each inbred generation. As a rule, lines were homogeneous after 7-8 generations.Results and discussion. The information on the genealogy of 38 lines developed by the researches of VIR, two VNIIMK lines, 16 foreign lines, and also the data on the origin of the CMS PET1 source are analyzed. The genealogical overview of the lines has allowed us to draw a conclusion on the origin of the high oil content and high oleic content traits. It is these characters that in the first place distinguish cultivated sunflower from the wild species of the genus Helianthus L. Lines originated from one and the same variety can differ by the presence of diagnostic markers of the Rf1 gene controlling pollen fertility restoration in forms with cytoplasmic male sterility, and also by allelic variants of storage protein genes and morphological characters.